Advantages of Teaching English with the Help of Electronic Didactic Tools-Mobile Devices (Journal of Pedagogical Inventions and Practices, 2023)
The modern trend of information technology can be considered to be miniaturization of computing equipment, that is, the emergence of mobile devices. In particular, the characteristics of modern smartphones are no less than the computing characteristics of personal computers developed a few years ago, and in most cases even prevail. This article reflects on the possibilities, advantages and convenience of new modern didactic tools entering the field of education with the development of digital pedagogy.